72.6k views
2 votes
Evaluate (1+√2)³+(1-√2)³



2 Answers

6 votes

Answer:

14

Explanation:

User Cclogg
by
5.8k points
0 votes

Answer:

14

Explanation:

Evaluate


(1+√(2))^3 + (1-√(2))^3

As we have the Cube binomials:


\boxed{(a+b)^3=a^3+3a^2b+3ab^2+b^3}


\boxed{(a-b)^3=a^3-3a^2b+3ab^2-b^3}


(1+√(2))^3 =1^3 + 3\cdot 1^2 \cdot√(2) + 3 \cdot 1 \cdot (√(2)) ^2 + (√(2)) ^3 = \boxed{7+5√(2)}


(1-√(2))^3 =1^3 - 3\cdot 1^2 \cdot√(2) + 3 \cdot 1 \cdot (√(2)) ^2 - (√(2)) ^3 = \boxed{7-5√(2)}


\therefore (1+√(2))^3 + (1-√(2))^3 =7+5√(2) + 7-5√(2) = \boxed{14}

User Awijeet
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.